Conservation of the group Piperia (Orchidaceae) and associated plant communities - Lauri, Robert (Universidad de Costa Rica, 2015)
The conservation and protection of California native orchids has not been a large focus recently. All California native orchids are terrestrial and many are associated with forest and woodland plant com- munities. However, a number are associated with the Mediterranean Climate plant community known as Chaparral; this includes at least three Piperia Rydb. species. Many Piperia populations and associated Chaparral plant communities have been impacted by human activity over the past several decades, howev- er, there is very little documentation regarding the size, and overall impact to the populations.